Appraising the performance of performance appraisals. - Goldstein, H.
As a ritual of corporate America, the days of the annual performance review may be numbered, thanks to managers and employees who've suffered through too many of them. They're the impetus behind a developing trend among US corporations to explore alternatives. That trend could have significant implications for employees across the globe, particularly in Japan, where an increasing number of firms are adopting, with varying degrees of success, the very sort of pay-for-performance systems that US companies are considering abandoning. In theory, of course, appraisals do more good than harm. They are intended to furnish valuable feedback to both employee and organization. But, say human resources experts, the so called objective criteria used to assess workers are flawed metrics. This is especially true when it comes to judging engineers and other professionals, who today often work not as individuals, but as members of teams on projects of variable duration. This paper discusses the drawbacks to appraisals and suggests that appraisals try to do too much. Alternatives to pay-for-performance are discussed focusing on better use of feedback and a clearer career ladder
Keywords: US corporations; Employee; Organization; Pay-for-performance systems; Performance appraisals; Team members; Variable duration projects